Structure and Composition of Major Arbuscular Mycorrhiza (MA) under Different Farmer Management of Coffee and Pine Agroforestry System - Prayogo, Cahyo; Prastyaji, Dimas; Prasetya, Budi; Arfarita, Novi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Utilization of Arbuscular Mycorrhiza (MA) as beneficial soil microbes is expected to support nutrient demand for improving crop performance. However, under the agroforestry system that facing a problem on light, water, and nutrients competitions, the role of MA is becoming unclear. The purpose of this research was to examine how far different management in Coffee Pines Agroforestry System (CPAS) affects MA structure and compositions. The relationship between soil parameters (e.g. pH, soil organic C) and MA activities was also being evaluated. The selected plot according to existing management practices were chosen as follows: (1) Low management (LC); (2) High management which then compared to (3) Business As Usual (BAU) plot in which were repeated in triplicate. ANOVA and multivariate analysis were employed to determine the effect of the treatments. The result showed that there were significant differences (p<0.05) in the structure and composition of the MA, in terms of the total number of MA spores and the abundance of Glomus sp. under the coffee tree sampling point, while the lowest number was detected in Gigaspora sp. genera. The more intensive land management resulted in a higher abundance of MA biomass which then leads to increased soil P and uptake-P along with MA infection.